Valoración económica del recurso hídrico para la conservación de la microcuenca del Río Papallacta, Cuenca del Napo. - Ortiz Escobar, Mirian Guissela (2021)
This research started from a theoretical foundation on environmental economics. Of which the environmental economic valuation was highlighted as one of the tools currently most used to include the environmental goods and services that ecosystems provide within the economic analysis. The objective of this research work was to determine the economic valuation of the water resource for the Papallacta river micro-basin, using the opportunity cost method based on a numerical and descriptive analysis, managing mainly variables of precipitation, temperature and vegetation cover of the area. study. The study area was reduced to water recharge zones that are equivalent to 21,894.84 ha, with them the water balance was carried out and subsequently the valuation of the environmental resource. The total valuation for the entire water recharge zone is $ 5'457,428.65, where it was determined that the value of use per hectare of land per year is $ 249.30. In addition, priority zones were established for protection and conservation that have with a water supply of more than 1'000,000 m3 / year. This study contributes as a model tool for decision-making and the formulation of specific policies and actions concerning the efficient use of water from the Papallacta river micro-basin.